Development of a Video-Test of Emotional Intelligence for Teachers (ViTIED) - María-Pilar Berrios-Martos; Raquel Palomera (Journal of Intelligence)
Emotional Intelligence (EI) in teaching is associated with various educational outcomes and processes. However, it has typically been measured through self-reports and general EI assessments, lacking a specific performance test with greater ecological validity in relation to the demands of the professional educational context. This study describes the development and validation results of the Video-Test of Emotional Intelligence for Teachers (ViTIED), a new performance-based measure to assess the EI of secondary education teachers based on ability EI model and the situational judgment test paradigm. The test comprises 12 video scenes designed to elicit intra- and interpersonal processes, as well as both positive and negative emotions. A total of 163 Spanish teachers (36% male, 64% female; mean age = 40.32 years) completed the ViTIED, along with personality, perceived EI, and burnout assessments. Test scores provide initial evidence of adequate reliability, as well as content, convergent, and divergent validity. Continued validation of this measure will benefit evaluation and intervention processes with teachers, as well as research on the impact of teachers’ EI on the teaching–learning processes and the well-being of the educational community.